The prevalence of hypothyroxinemia in premature newborns - Stawerska, Renata; Nowak-Bednarek, Marzena; Talar, Tomasz; Kolasa-Kicińska, Marzena; Łupińska, Anna; Hilczer, Maciej; Gulczyńska, Ewa; Lewiński, Andrzej (Frontiers in Endocrinology, 2022)
It is recommended to measure TSH and FT4 serum concentration on 3-5th day of life (regardless of the bloodspot screening), for the congenital hypothyroidism detection in preterm and SGA newborns. The purpose of the study was to determine the prevalence and causes of hypothyroxinemia in preterm and SGA newborns to determine which of them require this procedure. We measured TSH, FT4 and FT3 serum concentration on 3-5th day of life in children born as preterm or SGA full-term, at our centre within three consecutive years. We assessed the incidence of hypothyroxinemia, its cause: primary, secondary hypothyroidism or low FT4 syndrome - with normal TSH concentration, its dependence - among others - on gestational age (GA), birth body weight (BBW) and being SGA. A total of 525 preterm and 23 full-term SGA children were examined. FT4 concentration was decreased in 14.9% preterm newborns. The most frequent cause of hypothyroxinemia was low FT4 syndrome (79.5%). In more than 92% cases, hypothyroxinemia was observed in children born before the 32nd week (27.6% cases in that group) and/or born with BBW below 1500 g (25.3% cases). Neonates with hypothyroxinemia were significantly lighter than those with normal FT4. In older and heavier neonates with hypothyroxinemia serious congenital defects were observed. Neither IVH nor SGA nor twin pregnancies predispose children to hypothyroxinemia. Conclusions: Among newborns with untreated hypothyroxinemia in whom TSH and FT4 assessment was repeated within 2-5 weeks, a decreased FT4 concentration was confirmed in 56.1% cases. As hypothyroxinemia affects 25% newborns born before the 32nd week of gestation and these in whom BBW is less than 1500g, it seems that in this group of children the newborn screening should be extended to measure serum TSH and FT4 concentration between the day 3-5th of life. In older and heavier neonates, additional serum TSH and FT4 assessment should be limited to children with severe congenital abnormalities but not to all SGA or twins. Despite the fact that the most common form of preterm hypothyroxinemia is low FT4 syndrome, it should be emphasized that FT4 remains lowered on subsequent testing in more them 50% cases.